The inert firm; why old firms show a stickiness to their location - Aleid E. Brouwer (European Regional Science Association (ERSA), 2004)
This paper investigates the tendency of older firms to show stickiness to their home-region or fixed location, with the increase of age (in years since founding), as found in earlier research. Empirical evidence supporting this argument is found from a telephone survey under the population of old firms in the Netherlands. In the current paper an analysis is done to determine which other firm characteristics -next to age in years-, influence this stickiness to place; such as innovative behaviour, network relationships, market, size (in number of employees), region and location type. This analysis is done on written questionnaires of 179 firms in the Netherlands, 37 of these firms are specifically labelled as `old firms' (founded before 1851). Tested is whether inert behaviour, which according to the theory of structural inertia increases with age, also has an influence on the location of firms. Furthermore, the relationship between the spatial environment and other firm characteristics is investigated.
Keywords: 330